Anisotropy of magnetoresistance in untwinned YBa₂Cu₃O₇₋δ single crystals - Vovk, R.V.; Nazyrov, Z.F.; Kruglyak, V.V.; Ogrin, F.Y. (Functional Materials, 2012)
In this work we study an influence of the disorientation angle between direction of constant magnetic field up to 15 kOe and ah-plane α ≡ ∠(H,ab) on the temperature dependences of the excess conductivity in the temperature interval of transition to superconducting state in untwinned YBa₂CU₃O₇₋δ single crystals with a small oxygen hypostoichiometry. At temperature T > Tc, the temperature dependence of the excess para-conductivity is interpreted within the Aslamazov-Larkin theoretical model of the fluctuation conductivity for layered superconductors. The cause of appearances of low temperature "tails" (para-coherent transitions) on the resistive transitions, corresponding to different phase regimes of the vortex-matter state is discussed. Remove selected